A Multi-centered Study to Evaluate the Efficacy and Safety of Amitriptyline and Mecobalamine in the Management of Neuropathic Pain - Kiran, Dr. Mayuresh Dilip; Sheikh, Shaheen Naseem; Pawaskar, Lalit Jeeevan (International Journal of Innovative Research in Medical Science, 2019)
Introduction: Neuropathic Pain (NP) is known as ‘nerve pain’- is a type of chronic pain that occurs when nerve in the central nervous system becomes damage or injured. An FDC of Amitriptyline a neuroanalgesia and Mecobalamine (Vitamin B12) a damage nerve rejuvenator have an important role in management of NP. Methodology: Of 786 registered, 666 patients completed the study. Efficacy assessment was made by reduction in mean VAS score and ≥50% reduction in NP was calculated at conclusion visit and used to determine the corresponding NNT which was calculated by using risk reduction. Safety assessment was made by inspecting the adverse events during trial. Results: Reduction in mean VAS score was from 7.3 (baseline) to 5.6 (day 30) and 3.9 (day 45). Nearly all the patients had experience ≥50% reduction in NP and NNT score of 1.21 which was calculated by using risk reduction parameter at conclusion visit. Overall 236 patients experience adverse events and were of mild to moderate intensity, sedation and drowsiness being dominantly seen. Conclusion: A combination of Amitriptyline and Mecobalamine was efficacious, safe and well-tolerated in management of Neuropathic pain (NP).